Alignment of Fabry–Pérot Cavities for Optomechanical Acceleration Measurements - Marina Rezinkina; Claus Braxmaier (Photonics)
The wave optics processes in a Fabry–Pérot cavity with a length of about tens of millimeters are considered. Such cavities are used, among other applications, in optomechanical accelerometers for precise measurement of displacement of moving elements. A Fabry–Pérot cavity formed by a spherical and flat mirror is considered. The influence of parameters characterizing the alignment of the Fabry–Pérot cavity mirrors and the laser beam on the appearance of the higher order modes is investigated using numerical modeling. It is shown that the angle of inclination of the flat mirror of the cavity greatly affects the occurrence of higher order modes in addition to the fundamental mode. The levels of displacement of the axis of a spherical mirror in the vertical direction which do not cause the emergence of higher order modes is shown. The influence of the degree of displacement of the laser beam axis in the vertical direction relative to the symmetry axis of the Fabry–Pérot cavity is also investigated.